Porphyria cutanea tarda: A novel mutation - Rajesh Patil; Bhavna Dhingra; Dinesh Asati; Garima Goel; Ujjawal Khurana; Girish Chandra Bhatt (Elsevier, 2016)
A 5 year old child with waxing and waning vesicobullous lesions on exposed parts since two years. Blood porphyrin levels were increased and Woods lamp revealed erythrodontia. DNA analysis showed the child was homozygous and both parents were heterozygous for a novel pathogenic mutation V256M in uroporphyrinogen decarboxylase gene, thus diagnosed as type II recessive form of porphyria cutanea tarda. The child responded to sunscreens and antioxidants.